A significant productive in vivo infection of resting cells with simian immunodeficiency virus in a macaque with AIDS. Issue 2 (1st February 2017) - Pahar, Bapi; Lala, Wendy; Kuebler, Dot; Liu, David
Abstract: Identifying the cells that can be infected with HIV in vivo and thus potentially persist as latent reservoirs is of high priority. Here, we report the major infected cells in a chronically simian immunodeficiency virus (SIV)‐infected macaque that developed AIDS and encephalitis. A majority of the infected cells were detected as non‐proliferating resting cells. SIV‐infected non‐proliferating resting cells were found to be playing an important role in viral pathogenesis, persistence, or reservoir formation.